Chemical and Biological Evaluation of the Oil and Seedcake from Seeds of a Greek Cardoon Cultivar as Potential Functional Vegetable Oil. Comparison with Sesame, Flaxseed and Extra Virgin Olive Oils - Elisavet-Foteini Varvouni; Konstantia Graikou; Olga Gortzi; Antigoni Cheilari; Nektarios Aligiannis; Ioanna Chinou (Foods, 2021)
Cynara cardunculus L. is a plant of the Mediterranean basin, known since antiquity as a food and for its therapeutic properties. The needs of the 21st century for the utilization of agricultural waste has led to the study of the seed oil of a Greek cultivar of Cynaracardunculus (GCCC) as potential nutritional oil, as large amounts of cardoon seeds are discarded. The sterol and fatty acid profile of cold-pressed seed oil was examined by gas chromatography-mass spectrometry GC-MS and compared with that of solvent extraction. Total phenolic content was determined and compared with well-known and widely appreciated edible vegetable oils; while, additionally, the total lignan content and nutritional value of cold-pressed oil revealed it as a potential dietary candidate. Furthermore, the seedcake (residue of cold-pressed oil extraction) has been studied exerting it as a good source of phenolics. Both GCCC oil and seedcake were tested for their antioxidant and enzyme inhibitory activities exhibiting higher activity compared to the sesame, flaxseed and extra virgin olive oils. According to the results, Cynara seed oil was shown to be a rich source of ω-6/-9 fatty acids and phenolics, highlighting, indicating that it could be a promising health-promoting vegetable oil, while the seedcake was revealed as a rich source of bioactive compounds.